Contemporary Perspective on Terrorism: A Literature Review - Syahputra, Alfin Reza; Hamid, Supardi (Graduate Program Magister Manajemen Pendidikan, 2024)
Terrorism is taking on more and more varied forms, acts, and networks as a result of changes in worldwide, so that international organizations and civil society play a significant role in the battle against terrorism. Counterterrorism includes law enforcement, deradicalization efforts, and threat detection all done concurrently and collaboratively. As international organizations, the UN and Interpol prepared the legal framework, offered technical assistance, and supported the worldwide response. It is advised to use technology, cooperate across sectors, and reinforce deradicalization and preventative methods in order to maximize effectiveness. Global organizations must strengthen cross-border reactions and policy coordination in order to stop radicalization and boost civil society participation in educational initiatives. The role of financial institutions in preventing the funding of terrorism must also be considered. Governments and security agencies at both the national and international levels must enhance cyber security, keep an eye out for online content that encourages terrorism, and invest in the development of detection and monitoring technologies like artificial intelligence (AI), which functions as a virtual police force.